2020
DOI: 10.1159/000507265
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Lung and Lobe Volumes between Supine and Standing Positions Scanned with Conventional and Newly Developed 320-Detector-Row Upright CT: Intra-Individual Comparison

Abstract: Background: No clinical studies to date have compared unilateral lung or lobe volumes between the supine and standing positions. Objectives: To compare lung/lobe volumes on computed tomography (CT) between these two positions and evaluate the correlation between the total lung volume and total lung capacity (TLC) on pulmonary function tests (PFTs). Methods: Thirty-two asymptomatic volunteers underwent both conventional CT (supine position) and upright CT (standing position), during deep inspiration breath-hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 25 publications
3
67
2
Order By: Relevance
“…Upright CT (prototype TSX-401R, Canon Medical Systems, Japan) was developed based on 320-detector row CT (Aquilion ONE, Canon Medical Systems, Japan). Upright CT also has 320-detector rows, and its performance is comparable to that of conventional supine CT as described previously 9,10 . Thus, both conventional CT and upright CT machines enable continuous or intermittent (repeated) axial scans covering 16 cm per rotation at the same position using 320 detector rows (4D-scan) and helical scans using 80 detector rows.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Upright CT (prototype TSX-401R, Canon Medical Systems, Japan) was developed based on 320-detector row CT (Aquilion ONE, Canon Medical Systems, Japan). Upright CT also has 320-detector rows, and its performance is comparable to that of conventional supine CT as described previously 9,10 . Thus, both conventional CT and upright CT machines enable continuous or intermittent (repeated) axial scans covering 16 cm per rotation at the same position using 320 detector rows (4D-scan) and helical scans using 80 detector rows.…”
Section: Methodsmentioning
confidence: 80%
“…The recent improvement in CT has resulted in shorter scanning times, and the latest 320-row detector CT scanner can image the whole head within 5 s using helical mode and obtain 3-dimensional images of the whole head over time (4-dimensional imaging) using a 16-cm coverage axial scan. Recently, in collaboration with Toshiba Medical Systems (currently Canon Medical Systems), we proposed and developed an upright 320-detector row CT scanner; this scanner can obtain images of subjects in a standing or sitting position 9,10 . Using this system, we found that gravity differentially affected the volume and shape of the vena cava within the torso depending on body position 10 .…”
mentioning
confidence: 99%
“…This study evaluated the shortest distance between the acromion and humeral head in the standing position by using a newly developed upright CT scanner with a 3D approach. 8,9 Measuring 3D AHD while standing straight was feasible, and the mean value of the 3D AHD of healthy participants without previous injuries was 7.3 mm, ranging from 4.7 mm to 14.0 mm. The AHD was greater in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…However, a novel upright CT scanner has been developed, which enables 3D whole-torso cross-sectional scanning in the standing position 8 and evaluation of the effect of gravity on the human body. 9 This study aimed to clarify the 3D minimum distance between the acromion and humeral head of normal shoulders in the standing position using an upright CT scanner and compare the AHD values with those obtained using conventional methods. We hypothesized that 3D measurement of the actual distance between the acromion and humeral head in the standing position is feasible using CT scans and that its AHD values differ from those obtained using 2D analysis or in the supine position.…”
Section: Introductionmentioning
confidence: 99%
“…A newly developed upright CT scanner, whose transverse 320 row-detector gantry includes a stand supporting the rotary section on either side with a linear motion rail and ball screw to move the scanner up and down, enables whole-torso cross-sectional scanning with a 3dimensional acquisition in the standing position [7] and evaluation of the effect of gravity on the human body [8]. The purpose of this study was to evaluate the 3dimensional alignment of the shoulder girdle in the supine position using a conventional CT scanner and in the standing position using a newly developed upright CT scanner and to assess the alignment changes of the girdle between these two positions.…”
Section: Introductionmentioning
confidence: 99%